COMPUTER SIMULATION METHODS FOR SOLVING PHYSICAL TASKS IN THE COURSE OF PHYSICS AT HIGH AND SECONDARY SCHOOLS - M. Babenko (Kherson State University, 2013)
The article considers issues of application of computer simulation methods in teaching process of the course of physics at high and secondary schools. It has been given an example of visualization of oscillation processes by different parameters of system based on SCM MATLAB that is conducive to deeper understanding of physical phenomena.